In the Remains of Progress : Utopia and Suffering in Brazilian Popular Entrepreneurship - Costa, Henrique, (Social Sciences E-Books Online, Collection 2025., 2025)
This book proposes an ethnographic approach to popular entrepreneurship based on the experience of the wageless life in Brazil. It starts from the historical premise that self-employment is at the heart of the popular way of life, whose main characteristic is the desire for autonomy. In turn, the global discourse of self-realisation carries a strong attempt at modernisation aimed at young people, but which is also capable of embarrassing older people. From the shopping streets, social entrepreneurship and Pentecostal cults, this process is giving shape to political conflicts that are redrawing the sense of community in São Paulo, the country's largest city. See Less